Assessing Morphological Changes of the Msimbazi River Using Satellite Images - Izdori, Fides; Alexander, Augustina C.; Mulungu, Deogratias M. M.; Mugisha, Lucius (Tanzania Journal of Engineering and Technology, 2023)
This study assessed historical morphology changes of the Msimbazi River in Dar es Salaam City, Tanzania, following heavy rainfall events using historical Google earth images. The erosion and sedimentation processes that cause morphological changes of a river are also associated with flooding within the river catchments. In this study, the bank-line movement, erosion and sedimentation areas and changes in river section width were analyzed under three-time periods: 2005- 2012, 2012- 2018, and 2018- 2020. Data shows that, the timing for floods coincides with the historical records for heavy rains. It was found that, area in the upper reaches of the river such as Kinyerezi suffer from river bank erosion most, as indicated by the large increase in river width. This has resulted into washing away of infrastructure including houses and loss of land. The river channel width at Kinyerezi has widened a lot since 2005, with some sections having widths of more than 90 m. On the lower reaches for example around Kigogo and Jangwani areas, deposition of the soil materials prevails, resulting into raised river bed and reduced river widths. As the river section an hence carrying capacity is reduced, inundation of river banks occurs. This is among the causes of river bank flooding reported at these areas whenever there is a heavy storm event. It is therefore recommended that interventions to solve the flooding events in Dar es Salaam city should also include preventing catchment and river bank erosion on the upstream areas. Keywords: Foods, Extreme event, Lands at images, Dar es Salaam, Sediment tranport